(untitled) (Research, Society and Development, 2023)
Glaucoma is damage to the optic nerve, associated with an increase in intraocular pressure (IOP) with a reference between 10 and 21 mmHg, with the main outcome being blindness. The research objective is to know the clinical and epidemiological profile of patients with glaucoma treated at a clinic in the city of Imperatriz - MA. Descriptive, retrospective study with a quantitative approach. Attendance records were studied to verify the rate of patients diagnosed with glaucoma. Data were acquired from a database (medical records) of patients seen from June 2020 to June 2022, in an emergency service at a private clinic, from August to September 2022. individuals assisted during this study period, only those diagnosed with glaucoma aged over 40 years, of both sexes, time of diagnosis and IOP were selected. The population of this study has a mean age of 70 to 79 years and the female gender prevailed. The main cause of the low vision found was untreated or inadequately treated glaucoma. Little is known about the pathophysiological processes of glaucoma and it is believed that its definition is still unfinished. Further research on the prevalence of glaucoma in the city of Imperatriz is suggested. The study results are consistent with the pre-existing literature. The diagnosis of a potentially large number of patients with glaucoma is a very complex task in terms of logistics and socioeconomic impact.